2014
DOI: 10.1152/ajpcell.00375.2012
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase G increases antioxidant function in lung microvascular endothelial cells by inhibiting the c-Abl tyrosine kinase

Abstract: Oxidant injury contributes to acute lung injury (ALI). We previously reported that activation of protein kinase GI (PKGI) posttranscriptionally increased the key antioxidant enzymes catalase and glutathione peroxidase 1 (Gpx-1) and attenuated oxidant-induced cytotoxicity in mouse lung microvascular endothelial cells (MLMVEC). The present studies tested the hypothesis that the antioxidant effect of PKGI is mediated via inhibition of the c-Abl tyrosine kinase. We found that activation of PKGI with the cGMP analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 61 publications
2
39
0
Order By: Relevance
“…Another study demonstrated the capability of imatinib to inhibit endothelial permeability induced by the inflammatory agents VEGF, thrombin, and histamine in human microvascular EC (11). Imatinib also protected against H 2 O 2 -induced increased permeability in an in vitro model of oxidative stress in mouse lung EC (57). Finally, a recent case report of a patient with systemic capillary leak syndrome described impressive reversal of vascular leak after imatinib treatment, suggesting the clinical potential of this approach (1).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another study demonstrated the capability of imatinib to inhibit endothelial permeability induced by the inflammatory agents VEGF, thrombin, and histamine in human microvascular EC (11). Imatinib also protected against H 2 O 2 -induced increased permeability in an in vitro model of oxidative stress in mouse lung EC (57). Finally, a recent case report of a patient with systemic capillary leak syndrome described impressive reversal of vascular leak after imatinib treatment, suggesting the clinical potential of this approach (1).…”
Section: Discussionmentioning
confidence: 91%
“…We previously reported that c-Abl mediates enhancement of the lung EC barrier by the potent agonists S1P or FTY720 (20,59). In contrast, other reports indicate that c-Abl mediates oxidative stress-induced hyperpermeability (57,58), whereas Arg mediates EC barrier disruption induced by thrombin or VEGF (2). Additional studies support both similar and distinct roles for c-Abl and Arg kinases in other cellular processes relevant to barrier function including focal adhesion and cytoskeletal dynamics (48,62).…”
mentioning
confidence: 90%
“…The effect of NO on the microvasculature is complex and not fully understood, with lines of evidence supporting both barrier protective and barrier disruptive behavior (149,726). For instance, cGMP may offer protection from oxidative stress in microvascular ECs (598) and ROS-induced endothelial barrier dysfunction in vitro (427), yet NO-induced elevations in cGMP levels have been implicated in permeability increases following high tidal volume ventilator injury in mice (551). The reasons for these discordant results is unclear; however, emerging evidence suggests that subcompartmentalization of messengers like cGMP, cAMP, kinases and eNOS (541) may allow variable effects on barrier function based on subcellular localization.…”
Section: Transduction Of the Barrier Disruption Signalmentioning
confidence: 99%
“…The Abl family kinases, c-Abl (Abl1) and A bl r elated g ene (Arg, Abl2), have recently emerged as key mediators of vascular permeability due to their well characterized roles in the dynamic regulation of the actin cytoskeleton and cell-cell and cell-matrix junctions 58 . Several groups have recently reported that the FDA approved Abl kinase inhibitor imatinib attenuates vascular leak induced by thrombin, histamine, vascular endothelial growth factor (VEGF), lipopolysaccharide (LPS), and oxidative stress 913 . Although the mechanisms are not fully characterized, it is clear that Abl kinase inhibition has potent and pleiotropic effects on vascular barrier function.…”
Section: Inflammatory Vascular Leak: Overviewmentioning
confidence: 99%